PENERAPAN MANAJEMEN SUMBER DAYA MANUSIA YANG BAIK TERHADAP KINERJA PERUSAHAAN - Imhar; Merry Tumundo (Lembaga Pengembangan Kinerja Dosen, 2022)
The purpose of this scientific journal is to measure how much influence the application of competent human resource management has on the performance of a employees in a company. Respondents in this study amounted to 100 employees using a qualitative descriptive approach. The data researched and processed is the result of observational interviews with employees. Based on observations and research that has been done, it can be concluded that the implementation of good human resource management in a company greatly affects the performance of employees in a company. If a company in it does not have good human resource management, then the performance of a company will not be good and maximal. Then a company really needs the implementation of good management, so that human resources can improve the performance of a company. In addition, the company can also grow and achieve the desired goals. With this scientific journal, it is hopes that it can be guide implementing good management in a company.